Targeting T Cell Activation and Lupus Autoimmune Phenotypes by Inhibiting Glucose Transporters - Li, Wei; Qu, Ganlin; Choi, Seung-Chul; Cornaby, Caleb; Titov, Anton; Kanda, Natalie; Teng, Xiangyu; Wang, Haiting; Morel, Laurence (Frontiers in Immunology, 2019)
CD4+ T cells have numerous features of over-activated cellular metabolism in lupus patients and mouse models of the disease. This includes a higher glycolysis than in healthy controls. Glucose transporters play an essential role in glucose metabolism by controlling glucose import into the cell from the extracellular environment. We have previously shown that treatment of lupus-prone mice with 2-deoxy-D-glucose, which inhibits the first step of glycolysis, was sufficient to prevent autoimmune activation. However, direct targeting glucose transporters has never been tested in a mouse model of lupus. Here, we show that CG-5, a novel glucose transporter inhibitor, ameliorated lupus-like symptoms in a spontaneous lupus-prone mouse model, B6.NZM2410.Sle1.Sle2.Sle3 (Triple-congenic, TC), and in a chronic graft-versus-host-disease (cGVHD) model of induced lupus. In vitro, CG-5 blocked glycolysis in CD4+ T cells, and limited the expansion of CD4+ T cells induced by alloreactive stimulation. CG-5 also modulated CD4+ T cell polarization by inhibiting Th1 and Th17 differentiation and promoting regulatory T (Treg) induction. Moreover, CG-5 treatment reduced lupus phenotypes including the expansion of germinal center B (GC B) cells, as well as the production of autoantibodies in both TC mice and cGVHD models. Finally, CG-5 blocked glycolysis in human T cells. Overall, our data suggest that blocking glucose uptake with a small molecule inhibitor ameliorates the symptoms of lupus, at least partially due to its inhibition of glycolysis in CD4+ T cells.